Quasilinear elliptic systems with measure data. (May 2017) - Leonetti, Francesco; Rocha, Eugénio; Staicu, Vasile
Abstract: We study the existence of solutions of quasilinear elliptic systems involving N equations and a measure on the right hand side, with the form − ∑ i = 1 n ∂ ∂ x i ( ∑ β = 1 N ∑ j = 1 n a i, j α, β ( x, u ) ∂ ∂ x j u β ) = μ α in Ω